Expanding Professionalism in Music and Higher Music Education A Changing Game - Westerlund, Heidi; Gaunt, Helena (SEMPRE Studies in The Psychology of Music, 2021)
This book addresses the need to rethink the concept and enactment of professionalism in music, and how such concepts underpin professional higher music education. There is an urgent imperative to enable the potential of professional musicians in our contemporary societies to be more fully realised, recognising both intense challenges that are currently threatening some traditional music practices, and significant scope for new practices to be imagined in response to deep veins of societal need. Professionalism encompasses the conduct, aims, values, responsibilities and ongoing development of a practising professional in the field. Professional higher music education engages both with providing future professionals with relevant education in particular craft skills, and with nurturing their visions for their work as artists in future societies. The major focus of the book is on performance traditions that have dominated professional higher education, notably western classical music.